2002
DOI: 10.1091/mbc.01-12-0576
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal Organization in Skeletal Muscle Lacking Desmin: Evidence for Cytokeratins Associated with the Membrane Skeleton at Costameres

Abstract: The sarcolemma of fast-twitch muscle is organized into "costameres," structures that are oriented transversely, over the Z and M lines of nearby myofibrils, and longitudinally, to form a rectilinear lattice. Here we examine the role of desmin, the major intermediate filament protein of muscle in organizing costameres. In control mouse muscle, desmin is enriched at the sarcolemmal domains that lie over nearby Z lines and that also contain ␤-spectrin. In tibialis anterior muscle from mice lacking desmin due to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
85
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 78 publications
10
85
1
1
Order By: Relevance
“…The fact that actin is linked primarily to the Z-disks of striated muscle suggests that it is unlikely to mediate all the connections between the contractile apparatus and costameres, (Lazarides, 1980;Thornell, 1992;Capetanaki and Milner, 1998). Ultrastructural evidence, as well as studies of mice lacking desmin due to homologous recombination, suggest that desmin-based intermediate filaments are important in linking the Z-disks of superficial myofibrils to costameres at the sarcolemma (Granger and Lazarides, 1979;Pierobon-Bormioli, 1981;Street, 1983;Shear and Bloch, 1985;O'Neill et al, 2002), perhaps through a plectin cross-linker (Hijikata et al, 2003). Consistent with this, two desminassociated proteins, syncoilin and desmuslin or synemin, have been shown to bind dystrobrevin, a ligand of dystrophin (Mizuno et al, 2001;Newey et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The fact that actin is linked primarily to the Z-disks of striated muscle suggests that it is unlikely to mediate all the connections between the contractile apparatus and costameres, (Lazarides, 1980;Thornell, 1992;Capetanaki and Milner, 1998). Ultrastructural evidence, as well as studies of mice lacking desmin due to homologous recombination, suggest that desmin-based intermediate filaments are important in linking the Z-disks of superficial myofibrils to costameres at the sarcolemma (Granger and Lazarides, 1979;Pierobon-Bormioli, 1981;Street, 1983;Shear and Bloch, 1985;O'Neill et al, 2002), perhaps through a plectin cross-linker (Hijikata et al, 2003). Consistent with this, two desminassociated proteins, syncoilin and desmuslin or synemin, have been shown to bind dystrobrevin, a ligand of dystrophin (Mizuno et al, 2001;Newey et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that some fast twitch muscle fibers in the desmin-null mouse retained normal costameres, suggesting that desmin is not necessary to align costameres with the underlying contractile apparatus (O'Neill et al, 2002). Because cytokeratins are expressed in developing muscle and in muscle tumors (Langbein et al, 1989;Miettinen and Rapola, 1989;Kosmehl et al, 1990), and reverse transcription-PCR procedures suggested that mRNAs encoding cytokeratins were present in muscle extracts (Ursitti et al, 2004), we looked for cytokeratins in adult skeletal muscle and found them concentrated near the sarcolemma at costameres (O'Neill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations